2021
DOI: 10.31219/osf.io/7zwpk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Memory precision for salient distractors decreases with learned suppression

Abstract: Attention operates as a cognitive gate that selects sensory information for entry intomemory and awareness (Driver, 2001). Under many circumstances, the selected information is task-relevant and important to remember, but it is also well known that perceptually salient non- target objects will capture attention and induce awareness even when they are irrelevant (Adams and Gaspelin, 2020). Recent studies have shown that task interference by salient distractors diminishes after repeated exposures, but the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…In the ERP study, target enhancement is related to the N2pc component, which is a 4 hemisphere-lateralized modulation that indexes the rapid reallocation of attention towards task-relevant information in visual search, when the target attracts more attention, the amplitude of the N2pc would be larger (Eimer, 1996;Hickey et al, 2009;Luck & Hillyard, 1994). The other is distractor suppression, which refers to how irrelevant or potentially distracting visual objects can be suppressed below baseline to reduce distraction (Gaspelin et al, 2015) and requires the involvement of visual cortex regions or/and frontal-parietal network (Adam & Serences, 2021;Geng, 2014;Serences et al, 2004;Won et al, 2022). For example, Serence et al(2004) found that neural activity in the visual cortex regions increased prior to stimulus onset when the probability of distractors was higher, suggesting that visual cortex is involved in distractor suppression.…”
Section: Introductionmentioning
confidence: 99%
“…In the ERP study, target enhancement is related to the N2pc component, which is a 4 hemisphere-lateralized modulation that indexes the rapid reallocation of attention towards task-relevant information in visual search, when the target attracts more attention, the amplitude of the N2pc would be larger (Eimer, 1996;Hickey et al, 2009;Luck & Hillyard, 1994). The other is distractor suppression, which refers to how irrelevant or potentially distracting visual objects can be suppressed below baseline to reduce distraction (Gaspelin et al, 2015) and requires the involvement of visual cortex regions or/and frontal-parietal network (Adam & Serences, 2021;Geng, 2014;Serences et al, 2004;Won et al, 2022). For example, Serence et al(2004) found that neural activity in the visual cortex regions increased prior to stimulus onset when the probability of distractors was higher, suggesting that visual cortex is involved in distractor suppression.…”
Section: Introductionmentioning
confidence: 99%